Whiteness, internationalization, and erasure: decolonizing futures from the Global South - Dutta, Mohan J. (Communication and critical/cultural studies, 2020)
The essay explores the mobility of Whiteness in networks of Communication Studies that posture themselves as speaking from the Global South. Depoliticized languages of de-westernizing, internationalizing, and decolonizing are often articulated by elites in North-South networks pushing neoliberal governmentality, erasing claims to radical equality that emerge from within socialist struggles in the Global South. In resistance, a radical framework of knowledge from the Global South emerges from within subaltern struggles for hegemony, achieved through (a) delinking from the metropoles of the North and (b) explicitly crafting a socialist anticolonial politics that names and dismantles Whiteness as a capitalist project.